Safety and effectiveness of etanercept for treatment of juvenile idiopathic arthritis: Results from a postmarketing surveillance. Issue 1 (2nd January 2018) - Mori, Masaaki; Sugiyama, Naonobu; Morishima, Yosuke; Sugiyama, Noriko; Kokubo, Takeshi; Takei, Syuji; Yokota, Shumpei
Abstract: Objectives: The objectives of this surveillance were to determine safety and effectiveness of etanercept in patients with juvenile idiopathic arthritis (JIA). Methods: In this postmarketing surveillance, patients aged 5–16 years with active polyarthritis JIA were treated with etanercept at the doses approved in the Japanese package insert. The occurrence and seriousness of adverse events (AEs) were assessed using the Japanese Medical Dictionary for Regulatory Activities version 15.1. Effectiveness was determined as the improvement from baseline in disease activity score in 28 joints (DAS28)–erythrocyte sedimentation rate (ESR), remission, and physician's assessment of overall improvement. The number of responders was expressed as a percentage. The last observation carried forward method was used to impute missing data. Results: Safety analysis included 102 patients; 22 patients experienced 36 treatment-related AEs, three of which were unexpected. None of the AEs were deemed to need special safety warnings. Effectiveness analysis included 87 patients. At 24 weeks, 29/46 (63.0%) patients demonstrated either good or moderate response in DAS28-4/ESR and treatment was assessed to be markedly effective or effective by physicians in 79/83 (95.2%) patients. Conclusions: These data are consistent with earlier reports showing that etanercept was effective and demonstrated no safety signals in patients with JIA.